Role of sodium-glucose cotransporter 2 inhibitors in cardiovascular events in patients with heart failure - Eva Muja; Letizia Giuseppina Floccari; Artan Simaku; Klodeta Grosha; Besim Lama; Ilirian Laçi (Italian Journal of Medicine)
Heart failure is a major cause of morbidity and mortality globally, with a significant impact on both patients’ quality of life and healthcare costs. Sodium-glucose cotransporter 2 inhibitors (SGLT2-I), initially developed for the treatment of type 2 diabetes mellitus, have attracted particular interest due to their therapeutic potential in patients with heart failure, regardless of the presence of diabetes. This study aims to evaluate the efficacy of antidiabetic drug therapy with SGLT2-I in the treatment of heart failure. Specifically, the question is whether SGLT2-I therapy is more effective than placebo in improving heart failure symptoms, regardless of the presence of type 2 diabetes. The search was conducted in the PubMed database, and the search strategy included “SGLT2-I and cardiac patients”. A total of 2580 articles were found. Randomized trials and cohort studies enrolling diabetic and non-diabetic patients diagnosed with heart failure with preserved and reduced ejection fraction were included. 11 studies were included in the meta-analyses, and the total number was 41,472 patients, of which 22,110 were patients treated with SGLT2-I and 19,362 were patients treated with placebo. The duration of follow-up was 9 to 42 months (3.5 years). The results of this meta-analysis indicate that the use of SGLT2-I is associated with a significant improvement in cardiovascular and renal status in heart failure patients with reduced and preserved ejection fraction, with or without type 2 diabetes.